Dispersion pattern interspecific association and population status of threatened plants on submontane and montane zones of Mount Gede-Pangrango National Park - WIHERMANTO WIHERMANTO (Biodiversitas Journal of Biological Diversity, 2004)
The Mount Gede-Pangrango National Park has an attractive landscape view of mount summits with its crater, genuine floraand fauna of tropical rainforest, and a mild weather. Exploitation is forbidden in the area, but in reality encroachments occur,which will lead to changes in plant population status, particularly for threatened species. The aims of the research were investigate the populations status, dispersion pattern and possible interspecific associations of threatened plant speciesoccurred in the sub montane and montane zones of the Mount Gede-Pangrango National Park. Most of the threatened species occurred in the park had clumped distributions and only one of those showed a regular dispersion, namely Symplocos costata. It should be realized that populations with a clumped dispersion tend to provide over or under estimation of abundance, indicating the need for a larger sampling unit to cover. Based on the association tests conducted, three species (Antidesma tetrandrum, Pinanga coronata, and Castanopsis javanica) were significantly associated with Saurauia bracteosa, while Altingia excelsa and A. tetrandrum with Symplocos costata, as they had association indices more 0.3 using Jaccard Index. Pinanga coronata seems to be relatively closely associated with Saurauia cauliflora, Altingia excelsa with S. bracteosa, and Castanopsis javanica with S. costata. In contrast, Pinanga javana, Calamus adspersus, and Rhododendron album had low degrees of association, indicating their low abundance and co-occurrence with other species. Seven species of threatened plants were recorded in the Mount Gede-Pangrango: 5 of which had been proposed to change in their status. They were Calamus adspersus from vulnerable (V) changed into vulnerable (V UD2)., Lithocarpus indutus from vulnerable changed into critically endangered, Pinanga javana from endangered changed into vulnerable, Rhododendron album from vulnerable changed into endangered, and Saurauia bracteosa from vulnerable changed into endangered.ïƒ£ 2004 Jurusan Biologi FMIPA UNS SurakartaKey words: dispersion pattern, interspecific association, population status, threatened plants, Gede-Pangrango National Park